Leverage biomaterials to modulate immunity for type 1 diabetes - Jing, Zhangyan; Li, Yuan; Ma, Yumeng; Zhang, Xiaozhou; Liang, Xin; Zhang, Xudong (Frontiers in Immunology, 2022)
The pathogeny of type 1 diabetes (T1D) is mainly provoked by the β-cell loss due to the autoimmune attack. Critically, autoreactive T cells firsthand attack β-cell in islet, that results in the deficiency of insulin in bloodstream and ultimately leads to hyperglycemia. Hence, modulating immunity to conserve residual β-cell is a desirable way to treat new-onset T1D. However, systemic immunosuppression makes patients at risk of organ damage, infection, even cancers. Biomaterials can be leveraged to achieve targeted immunomodulation, which can reduce the toxic side effects of immunosuppressants. In this review, we discuss the recent advances in harness of biomaterial to immunomodulate immunity for T1D. We investigate nanotechnology in targeted delivery of immunosuppressant, biological macromolecule for β-cell specific autoreactive T cell regulation. We also explore the biomaterials for developing vaccine and facilitate immunosuppressive cells to restore immune tolerance in pancreas.